PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV - Soepardi, Khusnul Khatima; Musfirah; Nur Ilmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research employed a qualitative approach with a classroom action research (CAR) design. The main objective of the research was to understand how the implementation of the Project-Based Learning (PjBL) model could improve students' learning related to the socials and sains study. The research involved 16 students and one teacher during the 2024/2025 academic year, focusing on teaching process and student achievement. The instruments used included test, observation, and documentation. Data were collected through observations of the teacher and students, tests, and documentation, which were then analyzed in three stages: data condensation, data presentation, and conclusion. The research was conducted in two cycles, each consisting of two sessions with the stages of planning, implementation, observation, and reflection. The results showed an improvement in teacher activities from 55.5% in the first session of Cycle I to 88.8% in the second session of Cycle II. Student activities also increased from 59% to 83.3% during the same period. The evaluation revealed that the students' learning mastery level increased from 68.8% (Category C) in Cycle I to 87.5% (Category B) in Cycle II.The conclusion of this research is that the implementing of the Project-Based Learning model is effective in improving the learning process and achievement of fourth-grade students on the topic of energy transformation at UPTD SD Negeri 53 Parepare.